Template based precursor route for the synthesis of CuInSe2 nanorod arrays for potential solar cell applications - Pashchanka, Mikhail; Bang, Jonas; Gora, Niklas S. A.; Balog, Ildiko; Hoffmann, Rudolf C.; Schneider, Jörg J. (Beilstein Journal of Nanotechnology, 2013)
Polycrystalline CuInSe2 (CISe) nanorods are promising for the fabrication of highly efficient active layers in solar cells. In this work we report on a nanocasting approach, which uses track-etched polycarbonate films as hard templates for obtaining three-dimensionally (3D) arranged CISe nanorod arrays. Copper and indium ketoacidoximato complexes and selenourea were employed as molecular precursors. Arrays of parallel isolated cylindrical pores of 100 nm nominal diameter and 5 μm length were used for the infiltration of the precursor solution under inert atmosphere, followed by drying, thermal conversion into a preceramic ‘green body’, a subsequent dissolution of the template, and a final thermal treatment at 450 °C. The nanorods that where synthesised in this way have dimensions equal to the pore sizes of the template. Investigation of the CuInSe2 nanorod samples by spectroscopic and diffraction methods confirmed a high purity and crystallinity, and a stoichiometric composition of the CISe ternary semiconductor compound.
Keywords: CIS; light absorption; nanocasting; nanorod arrays; precursor synthesis